Perancangan Interior â€œReal Madrid Fc Fan Zoneâ€ di Surabaya - Abdisaputera, Denise Wiradinata; Santosa, Adi (Intra, 2013)
Pluralism community in Surabaya is vulnerable can make a difference, and therefore constituted of a sport football is most popular sport for all people created a Fan Zone at the base of a famous soccer team in the world, Real Madrid.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â The interior design goal is to provide a forum for people of Surabaya in general and football in particular who like to get a public facility that is open to everyone and to feel comfortable with and who can support the unity between people of very high levels of pluralism. Interior design according to the characteristics of Real Madrid, but it still shows the impression of openness and diversity of the application layout and materials and the atmosphere is presented.